2020
DOI: 10.14434/ijpbl.v14i1.28593
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Perceived Quality of Problems in the Association Between Achievement Goals and Motivation in Problem-based Learning

Abstract: The purpose of this study was to investigate the role of perceived problem quality in the relationship between students’ (N = 226) achievement goals and autonomous motivation to study in a problem-based learning (PBL) environment. Specifically, the relationships between students’ achievement goals (mastery-approach, performance-approach, performance-avoidance, and mastery-avoidance goals), problem quality-related characteristics (triggering interest, familiarity, stimulating collaborative learning, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…For example, students' motivation for going to college can differ before they have experienced the PBL method. A previous study has shown that individual differences in motivation can affect how students view certain aspects of the PBL environment, such as the quality of the problem (Noordzij & Wijnia, 2020). The current study examines if individual differences in students' motivation to go to college can affect their subsequent engagement in PBL meetings, their mood, and academic achievement.…”
Section: Objective (1991 Words)mentioning
confidence: 94%
“…For example, students' motivation for going to college can differ before they have experienced the PBL method. A previous study has shown that individual differences in motivation can affect how students view certain aspects of the PBL environment, such as the quality of the problem (Noordzij & Wijnia, 2020). The current study examines if individual differences in students' motivation to go to college can affect their subsequent engagement in PBL meetings, their mood, and academic achievement.…”
Section: Objective (1991 Words)mentioning
confidence: 94%
“…Path modeling is a type of SEM that provides a graphical representation of the relationships between variables. Compared to other methods, path modeling can be used to answer questions about direct and indirect influences between variables and identify the causal paths that lead from one variable to another, helping to visualize how changes in one variable can lead to changes in other variables (Kapur & Kinzer, 2007;Noordzij & Wijnia, 2020;Sockalingam et al, 2011). The methods presented thus far have focused on quantitative data, but to understand learning in action, we need to also consider qualitative methods for studying learning processes in PBL.…”
Section: Quantitative Methods For Visual Representationmentioning
confidence: 99%
“…Example of Path Analysis grounded in cognitive theory. Noordzij and Wijnia (2020) used path analysis specifically to investigate the relationship between the latent constructs of student achievement goals, problem quality-related characteristics, and autonomous motivation. Significant positive path coefficients established a direct impact of a few variables like problem familiarity and critical reasoning on the latent construct of autonomous motivation.…”
Section: Structural Equation Modeling and Path Analysismentioning
confidence: 99%
“…Interpersonal and interprofessional connections are visible through relationships, including social and family bonds, with ties to a place or environment (Cosgrave et al, 2019;Cranmer et al, 2017). Being familiar with people, places or work supports faster problem solving, efficiency, and increased confidence (Noordzij & Wijnia, 2020;Shen et al, 2020). Facing a familiar problem may increase one's confidence in having the ability to solve a problem versus tackling an unfamiliar one (Borgonovi & Pokropek, 2019).…”
Section: Empirical Referentsmentioning
confidence: 99%